VD_FINDINFO Décision / 2022 / 804 vom 21. Oktober 2022 - VD Tribunal cantonal (2022)
RISQUE DE COLLUSION, RISQUE DE RÉCIDIVE, DÉTENTION PROVISOIRE | 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH)